Synthesis and Activity Evaluation of Some Pyrazole–Pyrazoline Derivatives as Dual Anti-Inflammatory and Antimicrobial Agents. (14th September 2022) - Yan, Rui; Huang, Xiaoliu; Deng, Xianqing; Song, Mingxia
Abstract: In this study, 18 pyrazole derivatives coupled with pyrazoline were synthesized and screened for their anti-inflammatory and antimicrobial activities. All the target compounds were synthesized smoothly and characterized using 1 H NMR, 13 C NMR, and HRMS. In vitro lipopolysaccharide (LPS)-induced tumor necrosis factor (TNF)-α model and in vivo xylene-induced ear-edema model were used to evaluate their anti-inflammatory activity. Antimicrobial activity against several Gram-positive strains and Gram-negative strains was evaluated using a serial dilution method. Pharmacological results indicated that most of the compounds markedly inhibited the expression of TNF-α at the concentration of 20 μg/mL. Compounds 9b showed 66.4% inhibition for the LPS-induced TNF-α release, which was superior than that of the positive control drug dexamethasone (DXMS). And compounds 4a, 4b, 5a, 5b, 6b, and 9b showed comparable inhibition activity to DXMS. In xylene-induced ear-edema model, compound 4a inhibited edema by 48.71%, which was more effective than DXMS (47.18%) in inhibiting xylene-induced ear edema. Compound 4b, 5a, 5b, 6b, and 9b showed inhibition of 36.82%, 27.65%, 45.87%, 31.78%, and 43.67%, respectively. Furthermore, compounds 4a, 5a, 5b, and 9b displayed broad-spectrum antimicrobial activity against several Gram-positive and Gram-negative bacterial. These compounds, 4a, 5a, 5b, and 9b, possess both anti-inflammatory and antimicrobial activities, thus are worth further investigation to enhance their antimicrobial activities for the development of new class of dual anti-inflammatory–antimicrobial agents.